Problems and Solutions on Quantum Mechanics - Lim, Yung-Kno (Kolkata: SBH, 1998)
Lim$1 (Bs Problems and Solutions on Quantum Mechanics, published by Sarat Books, is a comprehensive book contains major American Universities Ph. D. Qualifying Questions and Solutions. It is compiled by The Physics Coaching Classes, University of Science and Technology of China. All concepts are explained in simple and lucid language for better comprehension.s
Index to problems 746-751p.; Reprint 2001.
Keywords: Electromagnetic fields; Perturbation theroy; Scattering theory; Central potentials